The role of marketing ingenuity in building an insight into customers / an exploratory study of the opinions of workers in the Oasis soft drink factory - Mahdi, Hawraa Thamer; Kamel, Suhad Barqi; Muhammed, Khmael Kamel (Eximia, 2023)
The research seeks to know the position of the management of the Oasis Soft Drinks Factory on marketing ingenuity and its employment in building customer insight and to show the impact of marketing ingenuity in its dimensions (exploring opportunities and exploiting opportunities) as an independent variable in building customer insight in its dimensions (customer behavior, customer attitude, customer culture) as a dependent variable. The research problem was identified in a number of points, the most important of which was the extent of the ability of the Karbala Oasis Soft Drinks Factory to build customer insight by adopting marketing ingenuity, and in order to achieve the goals of the research, the questionnaire form was adopted as a tool for data collection, and the Karbala Oasis Soft Drinks Factory was adopted as a study community where it was chosen A sample of its employees numbered (280).